Словникова робота в контексті сучасних вимог до навчання української мови (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
In the article are considered the questions of pupils’ vocabulary actualization of the context of modern Ukrainian language learning.